Pelatihan Dasar Kepemimpinan Dalam Membentuk Karakter Profesionalisme Pengurus OSIS Di Madrasalah Aliyah Al-Falah - Ahmad Azmy (LPPM Universitas Bina Sarana Informatika, 2021)
Basic leadership training is provided to provide preparation for all members of the organization in carrying out their duties professionally. Material directions are given to provide conceptual and applicable aspects of millennial leadership. Student council candidates are still not ready in terms of mentality and leadership. This training aims to provide a new perspective on the meaning of leadership and organizational governance. The training method is face-to-face directly to prospective OSIS Madrasah Aliyah Al-Falah administrators. The head of the organization leads a meeting and the effectiveness of communication for its members. Forming a professional leadership character for young people at Madrasah Aliyah Al-Falah in providing sufficient provisions with strong mentality. The preparation of this training will strengthen the intention and responsibility to carry out the position to advance the school organization in the future. So it can be concluded that basic leadership training is needed to shape the character of leaders in all prospective OSIS management at Madrasah Aliyah Al-Falah Jakarta.